ANALYSIS OF THE TRESTLE FOUNDATION ON SHIPS DOCKED IN CRUDE PALM OIL (C.P.O.) KABIL PORT BATAM CITY, INDONESIA. - Yusra Aulia Sari; Suhardi (Fakultas Teknik Sipil dan Perencanaan. Universitas Bung Hatta, 2021)
Batam Free Trade Zone (B.P. Batam) had established the first stage liquid bulk carrier port since 1987. In the beginning, that capacities transfer started from 70mt/hour to 150 mt/hour. Currently, it has developed the second stage plan within flow rate 300 mt/hour to 400 mt/hour. Port services consist of loading and unloading passengers, liquid, gas, and solid goods following PM 53 of 2018. The purpose of this study is to determine whether the depth of the trestle foundation is sufficient for the standards and requirements for ships berthed at the Port. The method used in this research is the quantitative approach. Data analysis was carried out by observation, interview, documentation, and investigation. The research period starts from early October 2020 to March 2021. In brief, the research results have shown that the depth of structure foundation trestle is safely constructed, adequate strength impact by respectively horizontal and vertical load factor for the vessel 35000 DWT berthing to jetty at Kabil Batam City.